Determinan Kinerja Keuangan pada Perusahaan Makanan dan Minuman yang Terdaftar di BEI Tahun 2021-2023 - Hanyfah Chairun Nisa; Endang Masitoh Wahyuningsih; Suhendro (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research was conducted to test and analyze the effect of independent board of commissioners, company size, leverage, and liquidity on financial performance. The data source used is secondary data obtained from the financial statements of food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The population of this study is food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. Sampling using the purposive sampling method and the sample used in this study amounted to 21 companies. The data analysis technique used multiple linear regression analysis processed with SPSS version 21. The results of the study show that independent board of commissioners, company size, leverage have an effect on financial performance. While liquidity does not affect financial performance.